A comparative study on the antifungal efficacy of cold atmospheric plasma at low and high surface density on Aspergillus chevalieri and mechanisms of action. (December 2022) - Molina-Hernandez, Junior Bernardo; Capelli, Filippo; Laurita, Romolo; Tappi, Silvia; Laika, Jessica; Gioia, Luisa; Valbonetti, Luca; Chaves-López, Clemencia
Abstract: Cold atmospheric plasma (CAP) is a promising innovative technology for microbial inactivation on food surfaces. In this study, we evaluated the potential of CAP at low (CAP-O3 ) and high (CAP-NOx ) power using Aspergillus chevalieri as a fungal model, one of the most xerophilic and xerotolerant molds causing food spoilage, We observed a strong reduction in mycelial growth (60%) and conidial germination (90%) after 30 min of CAP-NOx, while CAP-O3 was less effective showing no reduction in mycelia growth and only 36% of spore germination reduction. Furthermore, cell death was accompanied by a loss of cellular and mitochondrial potential membrane, a significant ( p < 0.05) increase in intracellular ROS, RNS, calcium, and DNA damage. For the first time, we reported that trehalose, glycerol, chitin and glucan accumulation are some adaptive mechanisms of A. chevalieri to counteract CAP stress, with CAP-NOx treatments inducing a major accumulation of these two osmolites. Our results suggested that Cold atmospheric plasma-induced cell death can be explained by oxidative stress-dependent through a cascade of reactions initiated by membrane depolarization. Highlights: Cold atmospheric plasma (CAP) under NOx regime was 60% more efficacious in reduce fungal growth than CAP-O3 regime. Reactive oxygen/nitrogen species (RONS) accumulation inside the cell contributed to depolarize the cellular membrane. CAP induced a reduction of the cytoplasmatic and mitochondrial membrane potential (ΔΨm). The Ca 2+ ion influx systems were increase for about 0.5 folds and 1.7 folds respectively for CAP-O3 regime and CAP-NOx. Aspergillus chevalieri PSJ144 responded to CAP stress accumulating trehalose, glycerol, chitin and glucan.